Proteomic Analysis of Serum and Urine of HIV-Monoinfected and HIV/HCV-Coinfected Patients Undergoing Long Term Treatment with Nevirapine - Wongtrakul, Jeerang; Thongtan, Thananya; Roytrakul, Sittiruk; Kumrapich, Benjawan; Janphen, Kanokwan; Praparattanapan, Jutarat; Supparatpinyo, Khuanchai; Smith, Duncan R. (Disease Markers, 2014)
Nevirapine (NVP) is an effective nonnucleoside reverse transcriptase inhibitor (NNRTI) of particular interest as it is often used in resource limited countries. However, one of the main concerns with the use of NVP is hepatotoxicity and elevation of liver enzymes as a consequence of highly active antiretroviral therapy (HAART) containing NVP is more often reported in HIV patients coinfected with hepatitis C virus than in HIV-monoinfected patients. To discover possible markers of NVP induced hepatotoxicity, serum and urine samples from twenty-five HIV or HIV/HCV patients, all of whom had received NVP continuously for at least four months, and healthy controls were subjected to in-solution or in-gel proteomic analysis. A total of 83 differentially regulated proteins consisted of 34 proteins identified in serum by in-solution analysis, 2 proteins identified from serum in a 2D gel electrophoresis analysis, and 47 proteins identified in urine in an in-solution analysis. Three proteins, namely, haptoglobin, Rho-related BTB domain containing protein 3, and death-associated protein kinase 3, were selected for further validation by Western blot analysis and results showed that haptoglobin has potential for further development as an additional marker of NVP induced hepatotoxicity.